Deskripsi Literasi Matematika pada Ruang Lingkup Pola Bilangan ditinjau dari Self Efficacy Siswa SMP - Talib, Ahmad; Rahman, Abdul; Auliah, Syarifah Rahmah (Issues in Mathematics Education (IMED), 2024)
This research aims to describe mathematical literacy in terms of self-efficacy in junior high school students. This research is descriptive qualitative. The sample used was selected based on the level of self-efficacy, namely high, medium and low. The instruments used were questionnaires, tests, and interview guidelines which had been validated by mathematics education lecturers with valid and usable results. The results showed that students with a high level of self-efficacy had good mathematical literacy because they met all indicators of mathematical literacy, students with moderate levels of self-efficacy had fairly good mathematical literacy because they only met two indicators of mathematical literacy, and students with low levels of self-efficacy had not good enough mathematical literacy because it only meets one indicator of mathematical literacy. In addition, there are also differences in self-efficacy in solving questions, that is, students with high levels of self-efficacy meet the indicators of generality, strength, and level. Students with moderate self-efficacy only meet level indicators and none of the indicators are fulfilled by students with low self-efficacy. It is hoped that future researchers will not only focus on analyzing mathematical literacy, but also look for the relationship between students' self-efficacy in solving problems